Design and the function of art - Anders Brix (Artifact, 2015)
Abstract Western thought tends to categorically separate art from “mere” artefacts: The arts serve no function except for aesthetic contemplation, while artefacts are functional objects intended for a specific purpose. This separation has caused some confusion as to the field of design, which may sometimes belong to either and at other times neither: not really art but not just utility. Thus the concept of design has fluctuated between the putative luxury of art and the practical necessity of technology. The beaux-art view saw design as an art form in its own right. Contemporary views, in contrast, tend to emphasize design’s capacities for problem solving, innovation and the like—to the extent of turning design itself into a “mere tool” for economic growth. This article examines how the art-artefact dichotomy, rooted in the notion of “function,” permeates contemporary design discourse. Through discussion of two examples, it reveals some of the logical inconsistencies the dichotomy gives rise to. Having demonstrated the shortcomings of such separation, it turns to discuss its origin in thought: Language separates, while things, as such, are whole. Further discussion of even more examples attempts to show how our perception of things is governed and directed by our discourses, and how this may cause us to overlook important features of both things in general and the potential of design in particular.